August 29th, 1787. At a meeting of the directors and agents of the Ohio Company : held at the Bunch of Grapes Tavern in Boston, the following report was received from the Rev. Menassah Cutler - Cutler, Manasseh, 1742-1823 ([Printed by Isaiah Thomas], 1787)
Describing the extent of the Northwest Territory and the terms for surveying and subdividing provided in the Ordinance of 1787.